Hubungan Status Pekerjaan Dan Pendapatan Orang Tua Di Masa Pandemic COVID-19 Terhadap Perilaku Pemberian ASI Esklusif - Mertasari, Luh (Bunda Edu-Midwifery Journal (BEMJ), 2021)
Covid-19, which cannot be predicted how long it will end, has changed and disrupted the economic system. Many families have lost their jobs and decreased income, which certainly threatens the exclusive breastfeeding program. The aim of the study was to determine the relationship between employment status and income during the Covid-19 period on exclusive breastfeeding behavior. Research method with literature study. The results showed that the employment status and income of parents had no effect on exclusive breastfeeding behavior, but large-scale social restrictions made parents have more time to breastfeed and concentrated on buying food to increase immunity rather than buying formula milk, so exclusive breastfeeding was the best choice.